Deploying the concept of agent-mediated knowledge management in mobile apps for collective decision making - Ismail S.; Ahmad M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Decision support systems; Knowledge based systems; Knowledge management; Management science; Multi agent systems; Robotics; Software agents; Agent-mediated knowledge management; Collective decision making; Communication medium; Decision making process; Group interaction; Interaction pattern; Mobile apps; Personal knowledge management; Decision making